Electrospun Nanofiber Meshes: Advancing the Science of Hernia Repair - Chandan Kumar Sahoo; Vishal Kumar Parida; Chopra, Hitesh; Inderbir Singh (Scripta Medica, 2025)
Hernia repair continues to be a major barrier in surgical practice, thereby necessitating the continued research for the development of novel methods for hernia repair which mainly focuses on patient compliance. This review paper focuses on the developing paradigm of the nanofiber meshes for the treatment of hernia. This review article summarises the conventional methods for hernia repair, development of the nanofiber mesh, their properties, characterisation and biological evaluation. The review outlines the advantages and disadvantages of nanofiber mesh being used for hernia repair. This review also highlights recent research work carried out on nanofiber mesh for hernia repair and different patent and marketed nanofiber mesh developed for treating hernia. In the end, this review promotes the use of nanofiber meshes as a viable direction for developing the area of hernia repair, providing better patient outcomes and addressing the shortcomings of conventional approaches.
Keywords: Nanofibers; Surgical mesh; Herniorrhaphy; Polypropylenes (PP); Polycaprolactone (PCL)